Era New Economy: Tantangan dan Harapan bagi Profesi Akuntan - Puji Harto (Jurnal Akuntansi dan Bisnis, 2004)
The fast improvement of science has emerged new economic era. The affect ofit to accountant has many concequences. In financial accounting field, the challengeof presenting financial information is relevancy. Information technology can be usedto improve relevancy, real-time information. In management accounting field, thereare many accounting contemporer concept which adapt to information technology. Inauditing field, the focus shift to assurance service. To face it, accountant mustimprove their quality by enhance information technology ability and inovate in doingtheir tasks.